Nasal carriage in Vietnamese children of Streptococcus pneumoniae resistant to multiple antimicrobial agents. - Parry, C; Diep, T; Wain, J; Hoa, N; Gainsborough, M; Nga, D; Davies, C; Phu, N; Hien, T; White, N; Farrar, J (2000)
Resistance to antimicrobial agents in Streptococcus pneumoniae is increasing rapidly in many Asian countries. There is little recent information concerning resistance levels in Vietnam. A prospective study of pneumococcal carriage in 911 urban and rural Vietnamese children, of whom 44% were nasal carriers, was performed. Carriage was more common in children <5 years old than in those >/=5 years old (192 of 389 [49.4%] versus 212 of 522 [40.6%]; P, 0.01). A total of 136 of 399 isolates (34%) had intermediate susceptibility to penicillin (MIC, 0.1 to 1 mg/liter), and 76 of 399 isolates (19%) showed resistance (MIC, >1.0 mg/liter). A total of 54 of 399 isolates (13%) had intermediate susceptibility to ceftriaxone, and 3 of 399 isolates (1%) were resistant. Penicillin resistance was 21.7 (95% confidence interval, 7.0 to 67.6) times more common in urban than in rural children (35 versus 2%; P, <0.001). More than 40% of isolates from urban children were also resistant to erythromycin, trimethoprim-sulfamethoxazole, chloramphenicol, and tetracycline. Penicillin resistance was independently associated with an urban location when the age of the child was controlled for. Multidrug resistance (resistance to three or more antimicrobial agent groups) was present in 32% of isolates overall but in 39% of isolates with intermediate susceptibility to penicillin and 86% of isolates with penicillin resistance. The predominant serotypes of the S. pneumoniae isolates were 19, 23, 14, 6, and 18. Almost half of the penicillin-resistant isolates serotyped were serotype 23, and these isolates were often multidrug resistant. This study suggests that resistance to penicillin and other antimicrobial agents is common in carriage isolates of S. pneumoniae from children in Vietnam.